Piezo1 and BKCa channels in human atrial fibroblasts: Interplay and remodelling in atrial fibrillation. (September 2021) - Jakob, Dorothee; Klesen, Alexander; Allegrini, Benoit; Darkow, Elisa; Aria, Diana; Emig, Ramona; Chica, Ana Simon; Rog-Zielinska, Eva A.; Guth, Tim; Beyersdorf, Friedhelm; Kari, Fabian A.; Proksch, Susanne; et al.
Abstract: Aims: Atrial Fibrillation (AF) is an arrhythmia of increasing prevalence in the aging populations of developed countries. One of the important indicators of AF is sustained atrial dilatation, highlighting the importance of mechanical overload in the pathophysiology of AF. The mechanisms by which atrial cells, including fibroblasts, sense and react to changing mechanical forces, are not fully elucidated. Here, we characterise stretch-activated ion channels (SAC) in human atrial fibroblasts and changes in SAC- presence and activity associated with AF. Methods and results: Using primary cultures of human atrial fibroblasts, isolated from patients in sinus rhythm or sustained AF, we combine electrophysiological, molecular and pharmacological tools to identify SAC. Two electrophysiological SAC- signatures were detected, indicative of cation-nonselective and potassium-selective channels. Using siRNA-mediated knockdown, we identified the cation-nonselective SAC as Piezo1. Biophysical properties of the potassium-selective channel, its sensitivity to calcium, paxilline or iberiotoxin (blockers), and NS11021 (activator), indicated presence of calcium-dependent 'big potassium channels' (BKCa ). In cells from AF patients, Piezo1 activity and mRNA expression levels were higher than in cells from sinus rhythm patients, while BKCa activity (but not expression) was downregulated. Both Piezo1-knockdown and removal of extracellular calcium from the patch pipette resulted in a significant reduction of BKCa current during stretch. No co-immunoprecipitation of Piezo1 and BKCa was detected. Conclusions: Human atrial fibroblasts contain at least two types of ion channels that are activated during stretch: Piezo1 and BKCa . While Piezo1 is directly stretch-activated, the increase in BKCa activity during mechanical stimulation appears to be mainly secondary to calcium influx via SAC such as Piezo1. During sustained AF, Piezo1 is increased, while BKCa activity is reduced, highlighting differential regulation of both channels. Our data support the presence and interplay of Piezo1 and BKCa in human atrial fibroblasts in the absence of physical links between the two channel proteins. Graphical abstract: Unlabelled Image Highlights: Piezo1 and BKCa are present and mechano-modulated in human atrial fibroblasts. Fibroblast Piezo1 activity is larger in atrial fibrillation compared to sinus rhythm. Fibroblast BKCa activity is smaller in atrial fibrillation compared to sinus rhythm. BKCa mechanosensitivity depends in part on stretch-activated Ca 2+ influx via Piezo1. Piezo1 and BKCa channels are linked functionally, but not structurally.